Eu Neonicotinoid Ban Removes Vital Tools in Global Fight Against Pests. (1st October 2018) - Blake, Robin
In May 2018, the European Union (EU) banned all outdoor uses of three neonicotinoid insecticides due to concerns about adverse effects on pollinators following their use. Neonicotinoids continue to be used in other areas of the world such as North America. However, increasing scrutiny following the European Union decision threatens their availability as a control tool for farmers in these regions too. This article aims to provide an update on the current status of neonicotinoids, including a brief overview of the reasons behind the European regulatory decision, alternative control strategies that are available to farmers, how the situation in Europe might influence what will happen in other regions of the world, and what this means for future regulatory decision-making. The author concludes that the recent neonicotinoid ban in the EU represents an overly conservative approach to pesticide regulation, and in using the Draft Bee Guidance Document, one where the majority of pesticides currently on the market will fail. There is no definitive scientific evidence that neonicotinoids are the primary cause of declines in bees, and although banning these insecticides is the factor that humans have the greatest control over, it represents an overly simplistic solution to a very complex problem, and one that alone may not improve bee health. Whilst extreme pressure from environmental NGOs and politicians have undoubtedly helped shape these decisions, it is imperative that the regulatory process allows scientific innovation to help achieve food security and protect the environment. Ruling against recent lawsuits brought by Syngenta and Bayer CropScience to contest the bans on their respective neonicotinoids, the General Court of the European Union, said that the EU's"precautionary principle" meant that the EU could take measures if there was scientific uncertainty about risks to human health or the environment. The precautionary principle lies at the heart of EU regulation and effectively puts the burden of proof to demonstrate that a pesticide poses no unacceptable risk onto the manufacturers. Given that neonicotinoids are insecticides, and insecticides kill insects, it is not difficult to connect how the use of the precautionary principle led to the neonicotinoid ban. However, this principle is at odds with the desire to innovate – the so-called "Innovation principle" – "whenever policy or regulatory decisions are under consideration the impact on innovation as a driver for jobs and growth should be assessed and addressed". The innovation principle and precautionary principle should be complementary, recognising the need to protect society and the environment while also protecting the EU's ability to innovate. Neonicotinoids represent one such innovation where their highly targeted nature, especially as seed treatments, makes them effective within Integrated Pest Management (IPM) strategies, in comparison to alternatives such as pyrethroids, organophosphates and carbamates, that are known to be highly toxic to bees (and other non-target invertebrates) through spray drift. Replacing neonicotinoids with these products will also result in higher overall environmental risks, including risks to taxonomic groups that are not adversely affected by neonicotinoids such as birds, mammals and fish, together with higher risks to humans, particularly applicators. The HFFA report recommends that potential environmental concerns must be balanced against the need to boost agricultural productivity, and if such an assessment results in societal benefits outweighing the costs, then the technology should be applied. The hope is that regulators in other regions of the world will judiciously balance innovation and precaution, and base decisions on science rather than opinion or fear, and thus allow the continued use of neonicotinoids as vital tools in the global fight against crop pests.